2020
DOI: 10.1002/chem.202002943
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Base‐Catalyzed Formal Reductive [3+2] Annulation of 4,4,4‐Trifluorocrotonate and α‐Iminoketones

Abstract: A formal reductive [3+2] annulation of 4,4,4‐trifluorocrotonate and α‐iminoketones was developed under Brønsted base catalysis. A single phosphazene base efficiently catalyzes the one‐pot tandem reaction involving two mechanistically different elementary processes, namely the chemoselective reduction of an imine moiety of α‐iminoketones with thiols as the reductant and the subsequent intermolecular Michael addition of an enolate of α‐aminoketones concomitant with lactam formation. This operationally simple met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Kondoh et al reported a formal reductive [3 + 2] annulation of 4,4,4-trifluorocrotonate 53 and α-imino ketones 52 under Brønsted base catalysis (Scheme 17). [21] The one-pot tandem reaction involves two mechanistically important processes, namely the chemoselective reduction of an imine moiety of αiminoketones with thiols as the reductant and the subsequent intermolecular Michael addition of an enolate of α-aminoketones concomitant with lactam formation, is efficiently catalyzed by a single phosphazene base 55. This straightfor- ward approach yields a single diastereomer of β-trifluoromethyl-substituted γ-lactams with a tetrasubstituted carbon.…”
Section: Other Annulation Reactions Of C-acyliminesmentioning
confidence: 99%
“…Kondoh et al reported a formal reductive [3 + 2] annulation of 4,4,4-trifluorocrotonate 53 and α-imino ketones 52 under Brønsted base catalysis (Scheme 17). [21] The one-pot tandem reaction involves two mechanistically important processes, namely the chemoselective reduction of an imine moiety of αiminoketones with thiols as the reductant and the subsequent intermolecular Michael addition of an enolate of α-aminoketones concomitant with lactam formation, is efficiently catalyzed by a single phosphazene base 55. This straightfor- ward approach yields a single diastereomer of β-trifluoromethyl-substituted γ-lactams with a tetrasubstituted carbon.…”
Section: Other Annulation Reactions Of C-acyliminesmentioning
confidence: 99%
“…An intuitive direct solution for the current restriction on substrates and intermediates would be the application of chiral Brønsted base catalysts having adequately high basicity . Indeed, our previous study with achiral Brønsted bases revealed that the use of strong Brønsted base catalysts is a rational and reliable strategy to establish a new type of tandem reaction using less acidic substrates and intermediates . In this context, we envisioned utilizing chiral organosuperbases, which have much higher basicity than conventional chiral organic bases, to develop an enantioselective reaction under asymmetric autotandem catalysis.…”
mentioning
confidence: 99%
“…In our previous study, we utilized the [1,2]-phospha-Brook rearrangement/β-elimination sequence for the catalytic ring opening of epoxides, in which the release of three-membered ring strain would serve as the driving force . In contrast, the present reaction requires the opening of a stable five-membered ring, and is thus more challenging . On the other hand, the direct transformation of alkenylphosphate into an α-functionalized ketone is rare, and the establishment of a new method for the second step is also essential.…”
mentioning
confidence: 99%
“…13 In contrast, the present reaction requires the opening of a stable five-membered ring, and is thus more challenging. 14 On the other hand, the direct transformation of alkenylphosphate into an α-functionalized ketone is rare, and the establishment of a new method for the second step is also essential. Based on the reaction design, we report herein a formal fluorinative ring opening of 2-benzoylpyrrolidine derivatives and a subsequent intramolecular reductive amination for the synthesis of 2-aryl-3-fluoropiperidines, which are difficult to synthesize by the reported intramolecular aminofluorination of alkenes.…”
mentioning
confidence: 99%